Non-Linear Behavior of Reinforced Concrete Frame Structure with Vertical Irregularities (International Journal of Innovative Research in Computer Science & Technology, 2023)
Various structural factors that contribute to  damage during an earthquake are vertical irregularities,  irregularities in strength and stiffness, mass irregularities,  torsional irregularities, and so on. Over the past decade,  performance-based design (PBD) procedures have become  one of the most critical areas in earthquake engineering. The pushover procedure is divided into two parts; the first  is the displacement target for the erected building. The  target is the estimated displacement of the top of the  building when exposed to the design earthquake excitation.  Then a pushover analysis is carried out on the building until  the top removal is equal to the target displacement. Second  is the type of controlled force in which the total amount of  force acting is estimated and applied to the structure, and  analysis is carried out.  The various performance levels for a building are expressed  in terms of the base shear carried versus the roof  displacement. If all the plastic hinges formed are within the  CP limit, the structure is said to be safe. On the other hand,  if the plastic hinge formed exceeds the CP limit, the  structure is said to have collapsed. This paper proposes a  2D reinforced concrete frame with three models with  variations of vertical irregularity. This paper aims to see the  nonlinear behavior of reinforced concrete frames with  vertical irregularities through the pushover method using  SAP2000 software. Furthermore, the analysis results show  that the skeleton is susceptible to increasing vertical  irregularity. As the vertical irregularity increases, the  percentage of the plastic hinge crossing the boundary  increases. The analysis results also show that model 2 has  better behavior.
Keywords: Pushover; Reinforced; Concrete; Frame